Cognitive Stimulation of Executive Functions in Mild Cognitive Impairment: Specific Efficacy and Impact in Memory. (March 2015) - Moro, V.; Condoleo, M. T.; Valbusa, V.; Broggio, E.; Moretto, G.; Gambina, G.
Executive functions play an important role in the maintenance of autonomy in day-to-day activities. Nevertheless, there is little research into specific cognitive training for Mild Cognitive Impairment (MCI). We present the results of a program which aims to teach specific strategies and metacognitive abilities in order for patients to be able to carry out attentional and executive tasks. Two groups (A and B) were compared in a cross-over design. After the first evaluation, Group A (but not B) participated in a six month cognitive stimulation program. After a second assessment, only Group B received treatment and then a final evaluation was carried out on both groups. The results show that: i) both groups improved their performance as an effect of training; ii) improvements generalized to memory and general cognitive tasks; iii) in the interval without training, Group B's performance worsened and iv) Group A partially maintained their results over time.